Case Report: Successful Treatment of Steroid-Refractory Immune Checkpoint Inhibitor-Related Pure Red Cell Aplasia With Cyclosporin - Gérard, Alexandre; Romani, Serena; Van-Obberghen, Elise; Fresse, Audrey; Muzzone, Marine; Parassol, Nadège; Boscagli, Annick; Rocher, Fanny; Borchiellini, Delphine; Drici, Milou-Daniel (Frontiers in Oncology, 2020)
Anemia associated with Immune checkpoint inhibitor is usually hemolytic and regenerative. Cases of aregenerative pure red cell aplasia are rare, and typically improve upon drug discontinuation and after corticotherapy. We herein report a case of nivolumab-related erythroblastopenia refractory to steroids in a melanoma patient that improved only after treatment with cyclosporin. Nivolumab had been well tolerated for 2 months after being introduced as an adjuvant treatment. Hemoglobin level then progressively decreased from 12.7 g/dl as baseline value to a nadir of 4.3 g/dL despite transfusion with a total of 29 packed red blood cells in 3 months. Extensive workup including repeated bone marrow examinations led to the diagnosis of pure red cell aplasia. Anemia persisted despite nivolumab discontinuation and over a month of corticotherapy, but improved dramatically 3 days after cyclosporin initiation and did not recur upon cyclosporin tapering. The patient remains cancer-free 9 months after nivolumab withdrawal. This case highlights the under-recognized risk of erythroblastopenia in patients treated with immune checkpoint inhibitor and proves cyclosporin is a valid alternative for the treatment of steroid-refractive cases.